Nontsizi Mgqwetho's the nation's bounty: a prophetic voice towards an African literary theory - Nxasana, Thulani (Rhodes University, Faculty of Humanities, School of Languages, 2017)
This thesis seeks to examine the ways in which Africans and African scholarship in particular have relied on the West to lead the way in scientific inquiry, theory and ways of approaching literary texts thus the stunting effects of this in the growth and development of uniquely African literary scholarship and theorising. In his seminal work, Decolonising the Mind, Wa Thiong'o (1987a) stresses that "...how we view ourselves, our environment even, is very much dependent on where we stand in relationship to imperialism in its colonial and neocolonial stages; that if we are to do anything about our individual and collective being today, then we have to coldly and consciously look at what imperialism has been doing to us and to our view of ourselves in the universe" (Wa Thiong'o, 1987a, p.88). Although most African countries obtained their liberation decades ago, seemingly western cultural imperialism still dominates and plagues the African psyche; hence they largely look to the West and ways of the West for established and emergent theoretical conceptions. This thesis aims to interrogate popular western literary theories unquestioningly used to analyse African works, particularly feminism and post-colonial theory; furthermore, to show crucial factors not taken into account such as the evolving power dynamics in African societies, the role of the "sacred" or spirituality which often forms and informs the dynamics of the text, and lastly, based on the poetry of Nontsizi Mgqwetho, to advocate for the need for an African literary theory and put forward the essential tenets of such a theory. The poetry of Xhosa poet, Nontsizi Mgqwetho, is used to analyse the complexities and dynamics of African literary production written in African languages; her poetry is written in isiXhosa to a Xhosa audience, a far cry from the assumption that African literary texts are concerned with writing to the "centre" as post-colonial theorists claim. Her work explicitly provides Africans with an approach to overcome territorial and cultural imperialism; she sees within the African psyche and traditional values empowering modes of resistance against any type of domination and through her poetry illustrates meaningful ways that Africans can critically engage with and examine the positives and negatives of cultural exchange and or assimilation, and the effects thereof while at the same time remaining proudly Africa.
Keywords: Uncatalogued